2011
DOI: 10.4317/jced.3.e487
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic management of single rooted immature mandibular second molar with single canal using MTA and platelet-rich fibrin membrane barrier: A case report

Abstract: An immature tooth with pulpal necrosis and periapical pathology imposes a great difficulty to the endodontists. Endodontic treatment options for such teeth consist of conventional apexification procedure with and without apical barriers. Various materials have been tried as apical matrix in the past. This article demonstrates the newer concept of using platelet rich fibrin membrane as an apical matrix barrier for stabilization of MTA in root end apexification procedure. Platelet Rich Fibrin is an autologous fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Narang et al [92] came to a different conclusion, observing better efficacy of PRF than PRP and BC in promoting healing of periapical lesions. The high efficacy of PRF in REP and treatment of inflammation was also confirmed in other reports [72,91,93,94].…”
Section: Components Of the Pulp Regeneration Processsupporting
confidence: 83%
“…Narang et al [92] came to a different conclusion, observing better efficacy of PRF than PRP and BC in promoting healing of periapical lesions. The high efficacy of PRF in REP and treatment of inflammation was also confirmed in other reports [72,91,93,94].…”
Section: Components Of the Pulp Regeneration Processsupporting
confidence: 83%
“…Kathuria et al [ 11 ] reported the use of PRF and MTA in healing of periapical lesion in permanent mandibular second molar. The PRF matrix prevented the extrusion of MTA in periradicular tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The intrinsic incorporation of cytokines within the fibrin mesh allows for their progressive release over time (7–10 days) as the network of fibrin disintegrates. [24] Corso MD et al . reported that fibrin network allows for cellular migration, particularly for endothelial cells necessary for neoangiogenesis and vascularization.…”
Section: Discussionmentioning
confidence: 99%